Analisis Performa Lubricating Oil (L.O.) Cooler Tipe Plate Heat Exchanger Untuk Penggantian Heat Exchanger Tipe Shell And Tube Pada KM Spil Rumi - Adam Aryo Kirono; George Endri Kusuma; Muhammad Shah (Politeknik Perkapalan Negeri Surabaya, 2023)
There is a case on KM Spil Rumi in the form of Lubrcating Oil (L.O.) cooler damaged due to leakage. The existence of this case is the basis of this research to find an alternative replacement with a redesign. The methodology used in this research uses LMTD (Log Mean Temperature Different). Based on the calculation results, it is found that the shell and tube heat exchanger has a better overall convection coefficient value with a value of 538.98 W/m2.C compared to the plate heat exchanger with a value of 459.19 W/m2.C. Although the overall convection coefficient value of the shell and tube heat exchanger is greater, the shell and tube heat exchanger has an overdesign value that is too large at 74.42%. Therefore, the plate heat exchanger with an overdesign value of 31.39% has a higher effectiveness value with a value of 64.3% compared to the shell and tube heat exchanger with a value of 46.4%.